"Beyond the Cultural Obviousness" (2019-2023): Summary of the Seminar Cycle at the University of Lower Silesia in Wrocław - Kurantowicz, Ewa; Reinhard, Karolina; Rudnicki, Paweł (INSTED: Interdisciplinary Studies in Education & Society, 2023)
test